2017
DOI: 10.1074/jbc.m117.778720
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and aging diminish sirtuin 1 (SIRT1)-mediated deacetylation of SIRT3, leading to hyperacetylation and decreased activity and stability of SIRT3

Abstract: Sirtuin 3 (SIRT3) deacetylates and regulates many mitochondrial proteins to maintain health, but its functions are depressed in aging and obesity. The best-studied sirtuin, SIRT1, counteracts aging- and obesity-related diseases by deacetylating many proteins, but whether SIRT1 has a role in deacetylating and altering the function of SIRT3 is unknown. Here we show that SIRT3 is reversibly acetylated in the mitochondria and unexpectedly is a target of SIRT1 deacetylation. SIRT3 is hyperacetylated in aged and obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 50 publications
4
71
0
Order By: Relevance
“…Consistent with our results, increased acetylation of liver mitochondrial proteins has been reported under metabolic stress conditions such as long-term high-fat diet feeding and alcohol consumption (46,56). One recent study has also demonstrated that, in obese and aged mice, liver Sirt3 is acetylated, and that this modification decreased its activity and stability (46). Based on these reports, we take that initial loss of Sirt3 in Pal-treated cardiomyocytes and hearts of HF-HS diet-fed mice results from acetylation of Sirt3 in mitochondria, which could be a first step in the scheme of evolution of diabetic cardiomyopathy.…”
Section: Mechanism Behind Down-regulation Of Sirt3 and Sirt6 During Dsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with our results, increased acetylation of liver mitochondrial proteins has been reported under metabolic stress conditions such as long-term high-fat diet feeding and alcohol consumption (46,56). One recent study has also demonstrated that, in obese and aged mice, liver Sirt3 is acetylated, and that this modification decreased its activity and stability (46). Based on these reports, we take that initial loss of Sirt3 in Pal-treated cardiomyocytes and hearts of HF-HS diet-fed mice results from acetylation of Sirt3 in mitochondria, which could be a first step in the scheme of evolution of diabetic cardiomyopathy.…”
Section: Mechanism Behind Down-regulation Of Sirt3 and Sirt6 During Dsupporting
confidence: 93%
“…It is therefore likely that increased acetylation of mitochondrial proteins, including Sirt3, in diabetic hearts results from excess concentration of acetyl-CoA in mitochondria. Consistent with our results, increased acetylation of liver mitochondrial proteins has been reported under metabolic stress conditions such as long-term high-fat diet feeding and alcohol consumption (46,56). One recent study has also demonstrated that, in obese and aged mice, liver Sirt3 is acetylated, and that this modification decreased its activity and stability (46).…”
Section: Mechanism Behind Down-regulation Of Sirt3 and Sirt6 During Dsupporting
confidence: 92%
See 1 more Smart Citation
“…However, consistent with its cytoprotective function, NRF2 deletion in mice leads to increased sensitivity to radiation, oxidative damage and age-related disease pathologies [105,111]. Specifically, NRF2 knockouts display accelerated heart failure in a myocardial infarct model [112], enhanced retinal degeneration [113,114], bone loss [110,115,116], and deficits in bone and endothelial stem and progenitor cell populations [115,117].…”
Section: Nuclear Factor Erythroid 2-related Factor 2 (Nrf2)mentioning
confidence: 99%
“…Moreover, the amount of lactic acid, the glycolysis product, was two orders of magnitude higher in cancer cells than in the normal tissue. When the Warburg effect was discovered, an increased glycolysis in cancer cells under aerobic conditions was misinterpreted as evidence for respiration 112 …”
Section: Introduction: What Is the Warburg Effect?mentioning
confidence: 99%